Designing a Policy Model for Green Human Resource Management with an Emphasis on Spiritual Leadership in Medical Sciences Universities (Case Study: Shahroud University of Medical Sciences and Health Services) - Beheshti, Ahmad; Farhadi Mahalli, Ali; Tabari, Mojtaba; Matoufi, Alireza (Management Strategies and Engineering Sciences, 2025)
This article aims to design a policy model for green human resource management (GHRM) with an emphasis on spiritual leadership, using Shahroud University of Medical Sciences as a case study. Philosophically, the study is grounded in an interpretivist paradigm and follows an inductive approach. It is categorized as an applied-developmental study in terms of its objective and is considered descriptive in terms of the time frame for data collection. A qualitative research design was employed. The participant population consisted of faculty members and administrators of Shahroud University of Medical Sciences. Purposeful sampling was used, and theoretical saturation was achieved after 17 interviews. Data were collected using semi-structured interviews and a questionnaire based on a decision matrix. The validity of the interviews was assessed and confirmed according to four criteria: credibility, transferability, confirmability, and dependability, as evaluated by expert reviewers. The reliability of the interviews was estimated using the Holsti method at 0.627. The reliability of the interpretive-structural modeling (ISM) was also assessed, with an internal correlation coefficient of 0.83, indicating acceptable reliability. Thematic analysis of expert interviews was conducted using Maxqda software, and the structural relationships model was designed using interpretive-structural modeling via MicMac software. The findings revealed that spiritual leadership influences supervisory ethical regulations, ethics-oriented culture, and workplace spirituality. These components, in turn, affect green human resource policy. Furthermore, human resource policy impacts legal responsibility, ethical responsibility, and social responsibility. Ultimately, social responsibility, ethical responsibility, and legal responsibility lead to the realization of green human resources in the proposed model.